Textbook of diabetes - Holt, Richard I. G. (Wiley-Blackwell, 2010)
"The new Textbook of Diabetes has been restructured into 12 sections in one accessible volume and is designed with the busy diabetes care team in mind. As well as retaining the elements that have made it such a popular brand, such as the outstanding full colour illustrations and text design, the new edition sees even greater emphasis on the clinical aspects of diabetes, with new chapters on managing patients with diabetes, the treatment of diabetes, and the delivery and organization of diabetes care, including: Patient assessment in the clinic; Non-insulin parenteral therapies; New technologies for insulin administration; The role of the hospital multidisciplinary team. There is also a companion website accompanying the book containing essential bonus material such as: Over 150 interactive MCQ's to help you improve and test your clinical knowledge; All 500 figures from the book in a downloadable format to use in slides and presentations; Chapter pdfs and chapter references with full links to PubMed"--Provided by publisher.